2020
DOI: 10.35699/1983-3652.2020.24399
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of machine translation output

Abstract: Despite fast development of machine translation, the output quality is less than acceptable in certain language pairs. The aim of this paper is to determine the types of errors in machine translation output that cause comprehension problems to potential readers. The study is based on a reading task experiment using eye tracking and a retrospective survey as a complementary method to add more value to the research as eye tracking as a method is considered to be problematic and challenging (O’BRIEN, 2009; ALVES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…This is the author's version which has not been fully edited and content may change prior to final publication. Citation information: DOI 10.1109/ACCESS.2024.3366802 [58], [61], [64], [68], [86], [72], [74], [76], [78], [81], [85], and [93] largely focus on various aspects of machine translation, including methodologies, approaches, and applications. In contrast, references [29], [38], [53], [45], [40], [41], [42], [47], [48], [35], [60], [61], [63], [64], [87], [69], [70], [71], [82], and [89] examine the use of deep learning, neural networks, and related technologies in machine translation and natural language processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the author's version which has not been fully edited and content may change prior to final publication. Citation information: DOI 10.1109/ACCESS.2024.3366802 [58], [61], [64], [68], [86], [72], [74], [76], [78], [81], [85], and [93] largely focus on various aspects of machine translation, including methodologies, approaches, and applications. In contrast, references [29], [38], [53], [45], [40], [41], [42], [47], [48], [35], [60], [61], [63], [64], [87], [69], [70], [71], [82], and [89] examine the use of deep learning, neural networks, and related technologies in machine translation and natural language processing.…”
Section: Discussionmentioning
confidence: 99%
“…References [1], [3], [11], [30], [31], [51], [32], [39], [55], [72], [73], [78], [81], [85], [88], and [90] specifically examine the assessment of machine translation quality, metrics, and methodologies. References [21], [22], [50], [35], [78], [82], [83], [84], [85], and [91] provide a detailed analysis of machine translation pertaining to particular languages or dialects, including Arabic, Urdu, Sana'ani, and Moroccan Arabic. Furthermore, the evaluation and increase in machine translation quality were examined in [3], [21], [29], [32], [49], [58], [86], [75], [78], [80], [85], [87], and [92].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of non-professional users where acceptability of a machine-translated text from English into Lithuanian was tested, an eye tracking experiment revealed that the cognitive processing was greater, i.e., required a longer gaze time and fixation count, on machine translation errors in comparison with correct segments of text (Kasperavičienė et al, 2020 ). The machine-translated segments with errors required more attention and cognitive effort from the readers, but the results regarding overall acceptability of the raw machine-translated text obtained via a post-task survey did not correlate with the readers' gaze time spent on segments with errors.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Rimkutė et al (2007) emphasised the importance of MT quality assessment and discussed linguistic peculiarities that arise in the machine translation process. Among the later approaches for English to Lithuanian, machine translation quality evaluation for neural translation systems was conducted by Stankevičiūtė et al (2017) and Kasperavičienė et al (2020). However, one of the most valuable studies on the MT for English-Lithuanian quality evaluation was published by Petkevičiūtė and Tamulynas (2011), who determined the main indicators for translation quality as well as identified many practical translation problems faced by MT systems.…”
Section: Approaches To Machine Translation Quality Assessmentmentioning
confidence: 99%